Técnicas de confecção de prótese total imediata mucossuportada - Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP]; Medeiros, Rodrigo Antonio de [UNESP]; Sônego, Mariana Vilela [UNESP] (My University, 2014)
The immediate complete denture is a prostheses made prior to teeth extraction, that aims to re-establish the patient aesthetics and function immediately after the removal of the remaining teeth. The objective of this paper is to report the technical procedures during the manufacture of immediate prosthesis. The study reports the clinical steps prior to teeth extraction as well as the surgical and maintenance procedures. The immediate complete denture is a viable rehabilitation method, especially to restore patients’ self-esteem, aesthetics and function promptly. An accurate planning and manufactory beholds better results

Prótese total imediata é um aparelho reabilitador construído previamente à extração dos dentes remanescentes, com o objetivo de restabelecer a função e estética imediatamente após a exodontia desses elementos dentários. O objetivo deste estudo é relatar a técnica de confecção de prótese total imediata. O estudo relatou as fases clínicas antes da exodontia, durante o procedimento cirúrgico e controles periódicos para manutenção da prótese. Conclui-se que a prótese total mucossuportada imediata é um método de reabilitação viável e de grande importância para restabelecimento da auto-estima, conforto, estética e função do paciente, devendo ser bem planejada e confeccionada para obtenção dos melhores resultados.
Techniques to manufacture immediate full denture mucossuportada
Keywords: Denture; Acrylic resins; Surgery oral; Prótese total; Resina acrílica; Cirurgia bucal